Cellular Reprogramming as a Therapeutic Target in Cancer. Issue 8 (August 2019) - Xiong, Shumin; Feng, Ye; Cheng, Lin
Abstract : Cancer heterogeneity has long been recognized as an important clinical determinant of patient outcomes and, thus, many new cancer treatments have been designed to target these different cells. Despite the short-term achievements of current therapies, including chemotherapy, antiangiogenesis therapy, radiotherapy, and immunotherapy, the long-term success of cancer regression remains poor. Therefore, researchers have investigated a new property, cellular reprogramming, in cancer that not only contributes to the classic hallmarks of cancer, but also suggests that cancer is a dynamic event rather than a static cellular entity. Here, we discuss the mechanisms by which the cellular reprogramming of cancer cells can explain some of the phenotypic and functional heterogeneity observed among cancer cells. Highlights: Cellular reprogramming, mainly including reprogramming to pluripotency, dedifferentiation, and transdifferentiation, results in cells with stemness or plasticity, which can occur spontaneously or in response to stress. Conventional studies demonstrate that cellular reprogramming contributes to tissue regeneration; however, emerging evidence links this process to cancer stem cell generation, resulting in cancer initiation, development, and recurrence. Current cancer therapeutics, such as first-line chemotherapeutic drugs, induce cellular reprogramming in a portion of cancer cells to a stem cell or plastic state associated with poor outcomes. Anticellular reprogramming via targeting appropriate signals from genetic instability, epigenetic changes, cell death signaling, metabolic signaling, and cell fusion helps improve cancer treatment.